PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Dian Dame Tinambunan; Maman Fathurrohman; Etika Khaerunnisa (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2020)
This research is motivated by the low ability of student' mathematical problem solving which is one of the goals in learning mathematic. One effort to improve students mathematical problem solving skills is to use the Cooperative learning model type Numbered Head Together (NHT) which makes students learn more actively in learning mathematics. This study aims to determine the final achievement and improvement of students' mathematical problem solving abilities by using the Numbered Head Together (NHT) learning model in mathematics learning. This study uses a quasi-experimental method with nonequivalent pretest-posttest control group design. The sample of this study were class VII E as an experimental class and class VII D as a control class in SMP Negeri 9 Serang City. The instrument used in this study was a test of mathematical problem solving ability. Data from this study were analyzed using descriptive statistics and inferential statistics. The conclusion of this study is the final achievement and improvement of students' mathematical problem solving abilities by using the Cooperative learning model Numbered Head Together (NHT) is better than students who use expository learning models. Thus, the Cooperative learning model type Numbered Head Together (NHT) can be applied to improve the mathematical problem solving ability of junior high school students.  Keywords:  Mathematical Problem Solving Ability, Numbered Head Together (NHT) Learning Model